2013
DOI: 10.1111/jnc.12612
|View full text |Cite
|
Sign up to set email alerts
|

LPS antagonism of TGF‐β signaling results in prolonged survival and activation of rat primary microglia

Abstract: Accumulating evidence indicates that activated microglia contribute to the neuropathology involved in many neurodegenerative diseases and after traumatic injury to the CNS. The cytokine transforming growth factor-beta 1 (TGF-b1), a potent deactivator of microglia, should have the potential to reduce microglial-mediated neurodegeneration. It is therefore perplexing that high levels of TGF-b1 are found in conditions where microglia are chronically activated. We hypothesized that TGF-b1 signaling is suppressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 53 publications
5
17
0
Order By: Relevance
“…In addition, microglia had decreased expression of TGFβR1 following LPS, and this downregulation was prolonged in aged microglia. This finding is consistent with reduced bioavailability of TGFβ because the presence of TGFβ augments TGFβR1 expression on microglia (Mitchell, et al, 2014). Importantly, aged microglia activated with LPS in vivo and treated ex vivo with TGFβ had decreased IL-1β expression after TGFβ treatment (data not shown).…”
Section: Discussionsupporting
confidence: 79%
“…In addition, microglia had decreased expression of TGFβR1 following LPS, and this downregulation was prolonged in aged microglia. This finding is consistent with reduced bioavailability of TGFβ because the presence of TGFβ augments TGFβR1 expression on microglia (Mitchell, et al, 2014). Importantly, aged microglia activated with LPS in vivo and treated ex vivo with TGFβ had decreased IL-1β expression after TGFβ treatment (data not shown).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, this study revealed that LPS treatment reduced the level of α7nAChR in microglia and that conversely ACh increased α7nAChR expression. Consistent with this, LPS not only reduces TGF-β receptors that are involved in signaling of anti-inflammatory cytokine TGFβ 1, but also impairs ability of TGF-β 1 to regulate expression of inflammatory mediators (Mitchell et al, 2014). Collectively, these results suggest ACh inhibition of neuroinflammation may require the presence of a key downstream receptor, such as α7nAChR, on microglia.…”
Section: Discussionsupporting
confidence: 63%
“…Classical NF‐kB consists of the p65/p50 heterodimer and is a pivotal regulator in inflammatory reactions, driving proinflammatory cytokine gene expression in microglia [34]. TGF‐β signaling, a potent deactivator of microglia, is thought to act as an anti‐inflammatory cytokine [9] and down‐regulates cytokine production in LPS‐stimulated microglia via Smad phosphorylation [35]. The relationship between CX3CL1 (fractalkine) and its receptor (CX3CR1) is tightly regulated in the brain.…”
Section: Discussionmentioning
confidence: 99%